Clinical case of using the minimally invasive "burr hole" microsurgical approach in the lateral ventricle tumor surgery - David I. Pitskhelauri; Sergey A. Maryashev; Nikita S. Grachev (LLC "MEDIAFORMAT", 2023)
The case of the large lateral ventricle tumor total removal using the minimally invasive bilateral burr hole microsurgical approach is reported.